Diversity patterns of the rhizosphere and bulk soil microbial communities along an altitudinal gradient in an alpine ecosystem of the eastern Tibetan Plateau - Cui, Yongxing; Bing, Haijian; Fang, Linchuan; Wu, Yanhong; Yu, Jialuo; Shen, Guoting; Jiang, Mao; Wang, Xia; Zhang, Xingchang (Geoderma, 2019)
The diversity patterns and drivers of soil microbial communities in altitudinal gradients have recently received much attention. The rhizosphere is a focus of soil microbial communities, but the patterns and drivers of these communities have rarely been studied in alpine ecosystems. We used high-throughput Illumina sequencing to examine the community variations of bacteria, archaea and fungi between the rhizosphere and bulk soil along an altitudinal gradient in an Abies fabri (Mast.) community on Mount Gongga of the eastern Tibetan Plateau. Microbial alpha diversity and community structure varied significantly with altitude but not between the rhizosphere and bulk soil. Soil temperature and the carbon:nitrogen ratio were the primary drivers of the structures of the bacterial, archaeal and fungal communities, and altitude (geographic distance) contributed a small part (<3%) of the community variation, indicating that various edaphic factors were the key regulators of microbial-community variation. This consistency of the microbial communities between the rhizosphere and bulk soil in this alpine ecosystem could be attributed to low temperature and high nutrient content. The bacterial, archaeal and fungal communities were governed by specific environmental factors (total phosphorus content for bacteria; organic-carbon content, dissolved organic-carbon content, NH4+-N content and nutrient stoichiometry for archaea and NO3−-N content for fungi). The distinct environmental responses of the microbial taxa suggested metabolic separation and resource preferences of the belowground communities, even within the small-scale spatial distances in this alpine ecosystem. Our study suggested that the ecosystem harbored many microbial taxa with diverse nutrient preferences and metabolic characteristics and could thus potentially tolerate the soil environmental variation under a scenario of climate change. [Display omitted] •Microbes in rhizosphere and bulk soil are highly similar in the alpine ecosystem.•Microbial community varies significantly with altitude within the same vegetation.•Soil temperature and the C:N ratio are the key drivers of microbial communities.•Bacteria, archaea and fungi are respectively affected by TP, NH4+-N and NO3−-N.